Autoeficácia em amamentação e fatores interligados - Maria de Fátima Fernandes Santos Silva; Luciana Barbosa Pereira; Tadeu Nunes Ferreira; Ana Augusta Maciel de Souza (Universidade Federal do Ceará, 2018)
Objective: to verify maternal self-efficacy related to breastfeeding among postpartum women. Methods: analytical and cross-sectional research with 385 puerperal women. The Short Form of the Breastfeeding Self-Efficacy Scale and a questionnaire with obstetric and socioeconomic variables were used. The data were analyzed by the student t-test in the Minitab Windows program version 17. Results: the factors with statistical significance were planned pregnancy (p=0.003), guidelines received during prenatal care (p=0.003), vaginal delivery (p=0.021), suckling in the first hour of life (p=0.003), income greater than a minimum wage (p=0.029) and non-use of illicit drugs (p=0.023). Conclusion: the participants had a high score for self-efficacy in breastfeeding related to planned pregnancy, guidelines received during prenatal care, vaginal delivery, first suction before the first hour of life, not offering to the child other milks prior to the letdown, mother's knowledge about the minimum time of exclusive breastfeeding and the non-use of illicit drugs.